2020
DOI: 10.1002/pcr2.10145
|View full text |Cite
|
Sign up to set email alerts
|

Nucleation modalities in poly(lactide), poly(butylene succinate), and poly(ε‐caprolactone) ternary blends with partial wetting morphology

Abstract: Ternary biodegradable polymer blends of poly(lactic acid) (PLA), poly(butylene succinate) (PBS), and poly(ε-caprolactone) (PCL) with the composition 45/10/45 wt% and exhibiting partial-wetting morphology were prepared. In this morphology, the minor phase is present as self-assembled droplets at the co-continuous interface of the other two major phases. The crystallization of the components in the various blends was thoroughly investigated. Differential scanning calorimetry highlighted minor differences in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 62 publications
(137 reference statements)
0
3
0
Order By: Relevance
“…As previously known, the size of the dispersed micro-domains in immiscible blends is crucial and has a strong effect on the final crystallization behavior of the minor phase. 13 , 23 , 24 , 26 28 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As previously known, the size of the dispersed micro-domains in immiscible blends is crucial and has a strong effect on the final crystallization behavior of the minor phase. 13 , 23 , 24 , 26 28 …”
Section: Resultsmentioning
confidence: 99%
“… 11 , 12 Fenni et al 12 reported the nucleation effect of molten poly(ε-caprolactone) (PCL) and molten poly(butylene succinate) (PBS) on poly(lactic acid) (PLA) self-assembled droplets in their 45/10/45 PCL/PLA/PBS immiscible ternary blend. While in another work, Fenni et al 13 showed that in 45/10/45 PLA/PCL/PBS ternary blends, the PBS continuous phase was able to nucleate at the surface of the previously crystalline PLA. Several factors were claimed to control and affect surface nucleation, such as polarity of the polymers, 14 affinities between different components, 12 states of the interface, and surface roughness.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation